Pedagogical Reforms in the Initial Training of Moroccan Teachers: The Emergence of a New Training Paradigm and New Concepts - El Yadari Abdelbasset (European Scientific Journal, ESJ, 2024)
In recent decades, countries around the world, including Morocco, have undertaken far-reaching reforms of their education systems to improve performance and efficiency. The initial training of future Moroccan teachers has been the subject of an innovative reform, introducing a new paradigm conveying concepts conducive to change. This article examines why the change envisaged by the reforms has not taken place, focusing on the epistemological dimension. It analyzes the relationship between the signifier and the signified of three key concepts: professionalization, integrative alternation, and reflexivity. The reforms failed to bring about the desired changes because of epistemological drifts caused by semantic distortions and cognitive biases in the implementation of the transformation project. The success of the new educational paradigm depends not only on the intrinsic quality of the concepts but, above all, on their understanding, assimilation, and translation into practice. The major challenge lies in the ability to preserve the integrity of the paradigm throughout its deployment, from its theoretical conception to its application in the field.